(untitled) (Jurnal Abdimas Administrasi Kesehatan, 2021)
The national health insurance (JKN) mobile application is a form of digital transformation of the BPJS health business model which was originally in the form of administrative activities carried out at branch offices or health facilities, transformed in the form of an application that can be used by participants anywhere and anytime without time limits. The national health insurance (JKN) mobile application can provide convenience for BPJS users or the public. The convenience in question is like paying. BPJS changes participation data, knows family participant data, etc. The activity was held for 3 days, namely on November 9-11, 2020. These activities are carried out in the form of socialization. ITKES Wiyata husada Samarinda student participants who have paid dues and do not make a deposit, will have an active registered BPJS card, so participants automatically have the right to get services both at the first level at the designated service location according to the wishes of the participant and advanced level referral to the hospital by showing a referral letter. JKN mobile benefits are unlimited, which means that participants will continue to get access to health insurance as long as the application is still mobile on the participant’s cellphone